Comparison of the Orientation of the Corneal Steep Meridian Determined by Image-Guided System and Manual Method in the Same Eye - Ohashi T (Dove Medical Press, 2020)
Tsutomu Ohashi,1 Takashi Kojima2 1Ohashi Eye Center, Sapporo, Japan; 2Department of Ophthalmology, Keio University School of Medicine, Tokyo, JapanCorrespondence: Tsutomu OhashiOhashi Eye Center, Kita1-1 Hondori6, Shiroishi, Sapporo 003-0027, JapanTel +81-11-864-4656Fax +81-11-864-2344Email Ohashi@rainbow.ne.jpPurpose: To evaluate the difference between the preoperative marking methods for toric intraocular lens (IOL) implantations using an image-guided system (IGS) and the manual marking method in the same eye.Patients and Methods: In this retrospective case series, 82 patients (101 eyes) who underwent cataract surgery using both manual and IGS (VERION, Alcon  Laboratories) marking were enrolled. First, preoperative reference marks were placed at 6 o’clock and 3 or 9 o’clock position under slit-lamp biomicroscope in the outpatient department using the manual method. Using the reference unit of IGS, the ocular surface data were captured and overlaid. The difference was then measured (preoperative axis misalignment). In the operating room, the orientation of the steep meridian of the manual method was determined based on this reference mark under the surgical microscope. Just before surgery, the digital degree gauge of IGS was overlaid on the ocular surface, and the difference was then measured (total axis misalignment). We calculated the intraoperative axis misalignment by subtracting preoperative axis misalignment from the total axis misalignment.Results: Mean absolute preoperative, intraoperative, and total axis misalignment values were 3.87± 3.95 degrees, 5.46± 4.42 degrees, and 4.98± 4.49 degrees, respectively. In preoperative, intraoperative, and total misalignment, the ratios of 10 degrees or greater were 10 (14.7%), 12 (17.6%), and 20 (19.8%) eyes, respectively.Conclusion: The manual method that determines the fixed position of the toric intraocular lens (IOL) may cause large misalignment compared with the IGS, suggesting that using manual method could sometimes result in a large misalignment of toric IOL implantation.Keywords: cataract surgery, image-guided system, steep meridian, manual method